Characterizing wind, wave, and Stokes drift interactions in the upper ocean during Typhoon Doksuri using the COAWST model - Yaoyao Han; Changsheng Zuo; Zhizu Wang; Yucui Wang; Chengchen Tao; Xu Zhang; Juncheng Zuo (Frontiers in Marine Science)
The COAWST model is used in this study to simulate wind fields, wave fields, and Stokes drift during Typhoon Doksuri, aiming to reveal the dynamics of atmosphere-ocean-wave interactions under typhoon conditions. The COAWST model provides a more accurate simulation of typhoon wind speeds compared to ERA5 reanalysis data and the WRF model, and it offers a more precise representation of significant wave heights (Hs) than ERA5 reanalysis data and the SWAN model. The root mean square error (RMSE) of wind speed shows a reduction of 90.97% and 61.09% compared to ERA5 and WRF, respectively, resulting in an RMSE of 1.71 m/s. While the Hs correlation coefficient is 0.86. Comparative analysis indicates that COAWST has higher accuracy than WRF and ERA5, particularly in capturing the asymmetrical phenomena of wind and wave field. The high-value regions of the wind and wave fields are concentrated in the first quadrant around the typhoon center. The COAWST model output, combined with empirical orthogonal function (EOF) analysis and the Ekman-Stokes number, is used to quantitatively evaluate the contributions of wind and wave effects to ocean surface flow. The peak Stokes drift velocity reaches 0.73 m/s, with a maximum transport intensity of 13 m²/s and a transport depth of 20 meters. EOF analysis indicates that the first two modes explain over 88% of the Stokes transport. The first mode represents the spatial distribution of Stokes drift during the typhoon, while the second mode captures the temporal evolution of drift velocity. This study provides insight into atmosphere-ocean interactions during extreme weather conditions by using the COAWST model to analyze Stokes drift and its influence on ocean surface dynamics.